Struktur Kepemilikan, Profitability, Investment Opportunity, dan Kebijakan Dividen Perusahaan Non-Keuangan di Indonesia - Juliani, Meily; Kurniani, Melisa; Candra, Rudi (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p08, 2023)
The research aims to determine the relationship between ownership structure, profitability ratios and investment opportunities on dividend policy. The research sample includes companies listed on the Indonesian Stock Exchange and meeting the criteria. Testing was carried out on 350 secondary data from the period 2018 to 2022. Panel regression data was applied as a testing method with the best Random Effect Model (REM) regression model. The research results indicate that there is a significant positive influence between profitability on dividend policy and a significant negative influence between investment opportunity on dividend policy. Keywords: Dividend Policy; Ownership Structure; Profitability; Investment Opportunity